Con: Live High-Train Low does not improve sea-level performance beyond that achieved with the equivalent living and training at sea level - Jacobs, R. A. (High Altitude Medicine & Biology, 2014)
In summary, the basic premise of LHTL is flawed, the primary mechanisms proposed to improve sea-level performance repeatedly fail to demonstrate any reliability, and, most importantly, the empirical evidence of LHTL as an effective training modality to sea-level performance beyond that achieved with the equivalent living and training at sea-level alone is at best equivocal. siehe auch: http://online.liebertpub.com/doi/full/10.1089/ham.2013.1076